2017
DOI: 10.1123/jsm.2016-0232
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Marketing Relationships End? Findings From an Integrated Model of Sport Sponsorship Decision-Making

Abstract: With firms spending $60 billion on sponsorship annually, it has become an integral part of the marketing mix and is necessary for the survival of many sport organizations. Despite the importance of these partnerships, conditions that may jeopardize what can be a long-term relationship for both sides are underresearched. Utilizing survival analysis modeling to examine a longitudinal dataset of 69 global sponsorships, the purpose of this research is to isolate factors that predict the dissolution of such partner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
91
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(102 citation statements)
references
References 83 publications
10
91
0
1
Order By: Relevance
“…This result is in line with the research results carried out by Armstrong [22], which states that philanthropic sponsorship will have a stronger impact on improving the corporate image of commercial sponsorship. Another factor that influences consciousness and sponsorship attitudes is the fit between the sponsor and the sponsored subject [16,17,[23][24][25][26], as well as caution in the selection of sponsored subjects in order to avoid adverse effects [27][28][29][30][31]. Finally, the activation of sponsorship is highlighted as one of the factors that predispose the efficiency of the sponsorship investment [24,27,29,32,33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This result is in line with the research results carried out by Armstrong [22], which states that philanthropic sponsorship will have a stronger impact on improving the corporate image of commercial sponsorship. Another factor that influences consciousness and sponsorship attitudes is the fit between the sponsor and the sponsored subject [16,17,[23][24][25][26], as well as caution in the selection of sponsored subjects in order to avoid adverse effects [27][28][29][30][31]. Finally, the activation of sponsorship is highlighted as one of the factors that predispose the efficiency of the sponsorship investment [24,27,29,32,33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…While they found that external economic conditions play a significant predictive role, they also found that congruence between the sport property and commercial brand lessened the chances of dissolution. Increased clutter in the form of the sport property taking on more sponsor partners made dissolution more likely (35).…”
Section: Sponsorship and Organizational Culture Kevin Heiseymentioning
confidence: 99%
“…Relationship marketing as a research lensa theoretical framework Sponsors and sponsees engage in mutually beneficial and reciprocal relationships (Farrelly and Quester, 2005). However, currently, few studies have investigated sponsorships and their discontinuation from a relationship marketing perspective, despite the fact that such a lens has been proven to be helpful (Farrelly and Quester, 2005;Jensen and Cornwell, 2017). Morgan and Hunt (1994, p. 22) define relationship marketing as "all marketing activities directed toward establishing, developing and maintaining successful relational exchanges."…”
Section: Theorymentioning
confidence: 99%